People With Disabilities and Social Determinants of Health Discourses - Wolbring, Gregor (Can J Public Health, 2011)
Social determinants of health (SDH) are an important public health policy discourse and the concept and scope of SDH is debated within and outside of the public health field. This article concerns itself with the visibility of people with disabilities in existing SDH discourses. It employed a frequency analysis of Google and Google Scholar search hits obtained with the phrase “social determinants of health” in combination with various social groups and looked at the visibility of people with disabilities within key SDH documents, the Millennium Development Goals and some contemporary SDH such as energy, water and climate change security. It found that people with disabilities are much less visible than other social groups despite the major impact SDH have on this population.